Erythrocyte, Whole Blood, Plasma, and Blubber Fatty Acid Profiles in Oceanaria-Based versus Wild Alaskan Belugas (Delphinapterus leucas) - Todd L. Schmitt; Caroline E. C. Goertz; Roderick C. Hobbs; Steve Osborn; Stacy DiRocco; Heidi Bissell; William S. Harris (Oceans, 2022)
This investigation compared the fatty acid (FA) levels found in erythrocyte (RBC) membranes, plasma, whole blood (WB), and blubber from wild Alaskan (Bristol Bay) belugas (Delphinapterus leucas) (BBB, n = 9) with oceanaria-based belugas (OBB, n = 14) fed a controlled diet consisting of primarily herring (Clupea harengus) and capelin (Mallotus villosus). FA patterns in RBCs, WB, and plasma varied considerably between BBB and OBB animals. Focusing on RBC FA levels of known dietary origin, the OBBs had markedly higher levels of 20:1n9,11 and 22:1n9,11. RBC levels of these fatty acids were 1% and 0.2% in the BBBs, but 8.2% and 4.5%, respectively, in the OBBs (p < 0.05 both). These long-chain mono-unsaturated FAs (LC-MUFAs) are rich in herring and capelin but not in the prey species (i.e., salmonids, smelt, cod, and shrimp) generally available to BBBs. As for the marine omega-3 poly-unsaturated fatty acids [PUFAs; 20:5n3 (eicosapentaenoic acid) and 22:6n3 (docosahexaenoic acid)], the former was higher in the OBBs vs. BBBs (16% vs. 11%, p < 0.05), but the latter was low and similar in both (3.8% vs. 4%). Similar patterns were seen in the other sample types, except that DHA% was higher in BBB than OBB animals in both plasma (12.6% vs. 8.7%) and in blubber (12% vs. 4.9%) (p < 0.05). A physiologically important omega-6 PUFA, 20:4n6 (arachidonic acid) was approximately 2× higher in BBB than OBB within RBC (22% vs. 12%), WB (16% vs. 7%), plasma (11.5% vs. 4.6%) and blubber (4.6% vs. 2.4%), respectively. While blubber FAs have been evaluated historically and relatively easy to procure with biopsy darts in the field, this study proposes that blood-based FAs collected during health assessments or subsistence hunts, especially RBC or WB FAs, may be more convenient to handle using dried blood spot cards (DBS) with limited cold storage and simplifies shipping requirements, and may more accurately reflect tissue FA status.

Bayesian estimation of group sizes for a coastal cetacean using aerial survey data - Charlotte Boyd; Roderick C. Hobbs; André E. Punt; Kim E. W. Shelden; Christy L. Sims; Paul R. Wade (Marine Mammal Science, 2019)
Many small cetacean, sirenian, and pinniped species aggregate in groups of large or variable size. Accurate estimation of group sizes is essential for estimating the abundance and distribution of these species, but is challenging as individuals are highly mobile and only partially visible. We developed a Bayesian approach for estimating group sizes using wide‐angle aerial photographic or video imagery. Our approach accounts for both availability and perception bias, including a new method (analogous to distance sampling) for estimating perception bias due to small image size in wide‐angle images. We demonstrate our approach through an application to aerial survey data for an endangered population of beluga whales ( Delphinapterus leucas ) in Cook Inlet, Alaska. Our results strengthen understanding of variation in group size estimates and allow for probabilistic statements about the size of detected groups. Aerial surveys are a standard tool for estimating the abundance and distribution of various marine mammal species. The role of aerial photographic and video data in wildlife assessment is expected to increase substantially with the widespread uptake of unmanned aerial vehicle technology. Key aspects of our approach are relevant to group size estimation for a broad range of marine mammal, seabird, other waterfowl, and terrestrial ungulate species.

Investigation of molecular biomarkers as potential indicators of health in wild belugas (Delphinapterus leucas) - Ebru Unal; Caroline E. C. Goertz; Roderick C. Hobbs; Robert Suydam; Tracy Romano (Marine Biology, 2018)

Assessing the abundance of Bristol Bay belugas with genetic mark‐recapture methods - John J. Citta; Gregory O'Corry‐Crowe; Lori T. Quakenbush; Anna L. Bryan; Tatiana Ferrer; Myra J. Olson; Roderick C. Hobbs; Brooke Potgieter (Marine Mammal Science, 2018)
The Bristol Bay stock of beluga whales ( Delphinapterus leucas ) is genetically distinct and resides in Bristol Bay year‐round. We estimated the abundance of this population using genetic mark‐recapture, whereby genetic markers from skin biopsies, collected between 2002 and 2011, were used to identify individuals. We identified 516 individual belugas in two inner bays, 468 from Kvichak Bay and 48 from Nushagak Bay, and recaptured 75 belugas in separate years. Using a POPAN Jolly‐Seber model, abundance was estimated at 1,928 belugas (95% CI = 1,611–2,337), not including calves, which were not sampled. Most belugas were sampled in Kvichak Bay at a time when belugas are also known to occur in Nushagak Bay. The pattern of genetic recaptures and data from belugas with satellite transmitters suggested that belugas in the two bays regularly mix. Hence, the estimate of abundance likely applies to all belugas within Bristol Bay. Simulations suggested that POPAN estimates of abundance are robust to most forms of emigration, but that emigration causes negative bias in both capture and survival probabilities. Because it is likely that some belugas do not enter the sampling area during sampling, our estimate of abundance is best considered a minimum population size.

Satellite telemetry reveals population specific winter ranges of beluga whales in the Bering Sea - John J. Citta; Pierre Richard; Lloyd F. Lowry; Gregory O'Corry‐Crowe; Marianne Marcoux; Robert Suydam; Lori T. Quakenbush; Roderick C. Hobbs; Denis I. Litovka; Kathryn J. Frost; Tom Gray; Jack Orr; et al. (Marine Mammal Science, 2017)
At least five populations (stocks) of beluga whales ( Delphinapterus leucas ) are thought to winter in the Being Sea, including the Bristol Bay, Eastern Bering Sea (Norton Sound), Anadyr, Eastern Chukchi Sea, and Eastern Beaufort Sea (Mackenzie) populations. Belugas from each population have been tagged with satellite‐linked transmitters, allowing us to describe their winter (January–March) distribution. The objectives of this paper were to determine: (1) If each population winters in the Bering Sea, and if so, where? (2) Do populations return to the same area each year ( i.e ., are wintering areas traditional)? (3) To what extent do the winter ranges of different populations overlap? Tagged belugas from all five populations either remained in, or moved into, the Bering Sea and spent the winter there. Each population wintered in a different part of the Bering Sea and populations with multiple years of data (four of five) returned to the same regions in multiple years. When data were available from two populations that overlapped in the same year, they did not occupy the shared area at the same time. Although our sample sizes were small, the evidence suggests belugas from different populations have traditional winter ranges that are mostly exclusive to each population.

Movements of beluga whales ( Delphinapterus leucas ) in Bristol Bay, Alaska - John J. Citta; Lori T. Quakenbush; Kathryn J. Frost; Lloyd Lowry; Roderick C. Hobbs; Helen Aderman (Marine Mammal Science, 2016)
We describe the annual distribution of beluga whales ( Delphinapterus leucas ) in Bristol Bay, Alaska, using data from 31 satellite‐linked transmitters during 2002–2011. Bristol Bay has one of the largest and best studied Pacific salmon ( Oncorhynchus spp.) fisheries in the world, allowing us to link the seasonal distribution of belugas to that of salmon. During salmon migrations, beluga movements were restricted to river entrances. Belugas generally did not relocate to different river entrances or change bays during peak salmon periods. However, the location of belugas was not related to the number of salmon passing counting towers, suggesting that belugas were either selecting locations that were good for catching salmon or there were simply more salmon than belugas needed to supply their nutritional needs. The distribution of belugas expanded after salmon runs ended, and was greatest in winter when belugas ranged beyond the inner bays, traveling as far west as Cape Constantine. Belugas continued to frequent the inner bays in winter whenever sea ice conditions allowed, e.g ., when winds moved sea ice offshore; however, they were never located south of the southern ice edge in open water or outside of Bristol Bay.

Interyear differences in the offshore distribution of eastern North Pacific gray whales - Kim E. W. Shelden; David J. Rugh; Roderick C. Hobbs (Marine Mammal Science, 2012)

An assessment of shore‐based counts of gray whales - David J. Rugh; Marcia M. Muto; Roderick C. Hobbs; James A. Lerczak (Marine Mammal Science, 2008)
Counts of migrating whales depend on accurate sightings data. In this study, teams of shore‐based observers independently tracked whale pods during the southbound migration of gray whales ( Eschrichtius robustus ) while a routine (“standard watch”) census was underway. A comparison of sighting records showed that time and location accuracy was limited to 45 s, 3° (magnetic) horizontally, and 0.0057° (0.2 reticles) vertically. Of 242 attempts to track whale groups, 72 failed, 120 were “good tracks,” and 83 qualified as “best tracks” because they had ≥8 sightings/pod, ≥16‐min observation time, and unequivocal matches to sightings in the standard watch during uncompromised visibility. Between paired tracking teams, 39 attempts to conduct concurrent tracks resulted in 21 “good tracks” with complete agreement in 71% of the cases. Of 133 comparisons between trackers and the standard watch, 43% of the pod‐size estimates were the same, but the standard watch overestimated 10% of the pods and underestimated 47%. Thus, according to results from tracking teams, pods recorded as size 1 by observers on the standard watch should be corrected by +0.6; pods of 2 by +0.5; pods of 3 by +0.8; and pods >3 (4–10) were overestimated and should be corrected by −0.6.

EVIDENCE OF A FEEDING AGGREGATION OF HUMPBACK WHALES ( MEGAPTERA NOVAEANGLIAE ) AROUND KODIAK ISLAND, ALASKA - Janice M. Waite; Marilyn E. Dahlheim; Roderick C. Hobbs; Sally A. Mizroch; Olga Von Ziegesar‐Matkin; Janice M. Straley; Louis M. Herman; Jeff Jacobsen (Marine Mammal Science, 1999)

CALCULATING SIGHTING DISTANCES FROM ANGULAR READINGS DURING SHIPBOARD, AERIAL, AND SHORE‐BASED MARINE MAMMAL SURVEYS - James A. Lerczak; Roderick C. Hobbs (Marine Mammal Science, 1998)